Adaptation and Validation of the Malay Version of the Stress and Anxiety to Viral Epidemics-6 Items Scale Among the General Population - Pang, Nicholas Tze Ping; Tseu, Mathias Wen Leh; Gupta, Pradeep; Dhaarshini, Jaya; Kamu, Assis; Ho, Chong Mun; Ahmed, Oli; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
The coronavirus disease pandemic has caused untold distress owing to both its physical and psychological sequelae, and such distress is further exacerbated by multiple socioeconomic ramifications. The Stress and Anxiety to Viral Epidemics-6 Items (SAVE-6) Scale was developed to specifically assess the anxiety response of the general population to viral epidemics. This study aimed to establish the psychometric properties of the Malay version of the SAVE-6 Scale in the general population. Herein, a total of 257 individuals participated. World Health Organization instrument validation protocols were used to translate and back-translate the Malay SAVE-6 Scale. Subsequently, the classical test theory and Rasch analysis were used to ascertain the validity and reliability of the scale. Cronbach α was used to measure the internal consistency, which was found to be satisfactory (α=0.866). The correlations between the SAVE-6 Scale and other measurement scales, including the Generalized Anxiety Disorder-7 Items Scale (r=0.421, p<0.001) and Patient Health Questionnaire-9 Items (r=0.354, p<0.001) were significant. Taken together, the Malay version of the SAVE-6 Scale is valid and reliable for use in the general population and is psychometrically suitable for assessing stress and anxiety specific to viral epidemics.